Il torrente d’Egitto: nuove proposte per un vecchio problema di geografia biblica - Kaswalder, Pietro (Liber Annuus, 2008)
Abstract The article examines the function of the Brook of Egypt in the formulae of the southern border of Canaan. Since the greek translation of the Old Testament (LXX) and the Byzantine tradition (Eusebius’ Onomasticon, and the Madaba Mosaic Map), the border is identified as the wadi el-Arish. But the recent studies by N. Na’aman, P.K. Hooker, Y. Levin, K.D. Hutchens, J.C. de Vos, have brought forth new light on this subject. The Biblical texts (the Brook of Egypt) and the Neo-Assyrian sources (nahal mat Musur) suggest the identification of two different brooks in the southern region of Gaza: the wadi Azzeh (Nahal Besor) and the wadi el-Arish. It is reasonable to think that in the first stage of the history of this border the wadi Azzeh was considered to be a physical limit for the territory of Judah (Josh 15:1-4) and of Canaan. But after the military campaigns of Asharradon (7th century BCE) the border was transferred to the wadi el-Arish, some 75 km south. In addition, the redactional history of Josh 15:1-4 and Num 34:1-6 points to the literary dependence of the latter on the former. Other biblical formulations of the southern border of the Land of Israel try to adapt the concept of the Promised Land to a new political realitiy, as formulated by the Assyrian and the Persian empires.